WinMIgob: A Windows program for magnetite-ilmenite geothermometer and oxygen barometer - Yavuz,F. (Journal of Geosciences, 2021)
A Microsoft® Visual Basic software, called WinMIgob, has been developed for wet-chemical and electron-microprobe compositions of coexisting magnetite-ulvöspinel and ilmenite-hematite solid solutions to calculate the temperature (T, °C) and oxygen fugacity (fO2) conditions of magmatic and metamorphic rocks. The program allows the users to enter total of 34 input variables, including Sample No, SiO2, TiO2, Al2O3, V2O3, Cr2O3, Nb2O3, Fe2O3, FeO, MnO, NiO, ZnO, MgO, CaO, Na2O, K2O, BaO (wt. %) for each magnetite and ilmenite compositional data. WinMIgob enables to enter and load multiple magnetite and ilmenite analyses in the program’s data entry section. Alternatively, the composition of magnetite-ilmenite pairs can be typed in a blank Excel file as in the above order and then loaded into the program’s data entry screen for data processing. The ferric and ferrous iron contents from microprobe-derived total FeO (wt. %) of magnetite-ilmenite compositions are estimated by stoichiometric constraints based on three different approaches. Using the calculated multiple magnetite and ilmenite analyses, WinMIgob estimates molecular (%) and mole fractions of magnetite, uvöspinel, ilmenite and hematite amounts. The program evaluates fourteen magnetite-ilmenite geothermometers, thirteen oxygen barometers and six relative to the nickel-nickel oxide (NNO) buffer values based on the different calibrations with various calculation methods. WinMIgob also allows users to check if their magnetite-ilmenite pairs taken from rocks are within or departure from the Bacon-Hirschmann Mg/Mn exchange equilibrium line  2 level. This program generates and stores all the calculated results in the Microsoft Excel file (i.e., Output.xlsx), which can be displayed and processed by any other software for further data presentation and graphing purposes. The compiled program code is distributed as a self-extracting setup file, including a help file, test data files and graphic files, which are intended to produce a high-quality printout.
Keywords: magnetite; ilmenite; geothermometer; oxygen fugacity; Bacon-Hirschmann; software